SHOULD THE U.S. ADAPT TO THE WORLD? THE FIRST DEBATE ON AMERICAN EXCEPTIONALISM AND ITS IMPACT ON THE FOUNDING OF THE UNITED STATES - Ruiz, Jean-Marie (POLISSEMA – Revista de Letras do ISCAP, 2019)
This paper aims at putting into perspective the recent, post 9/11 debate on the United States’ alleged exceptionalism and its impact on the definition of American foreign policy. It reminds the readers that the United States was born as a result of a similar debate, at a time when a crucial choice for its future was to be made. Indeed, the Founding Fathers discarded the revolutionary idea that America was altogether different from other (European) nations and, as such, could succeed in saving republicanism and concentrate on domestic affairs. As Gordon Wood and Harvey Mansfield have shown, the 1787 version of republicanism stood as a departure from its earlier version, and such a change was necessary to the creation of a full-fledged federation, therefore paving the way to the current powerful Federal Republic. The early failure of the exceptionalist creed did not cause its disappearance, as the contemporary form of exceptionalism demonstrates, but created conditions that made an enduring and powerful influence very difficult.